Association between voice problems and noise effects among call center operators in the city of Campinas-SP (Research, Society and Development, 2022)
Objective. To investigate the associations between voice complaints and noise effects among call center operators in the city of Campinas-SP. Methodology. Observational and cross-sectional study carried out on 212 telemarketing operators of a company in the city of Campinas-SP. The procedures included the application of two instruments: questionnaire on noise annoyance and other effects and Voice Disorder Screening Index (VDSI). The statistical analysis used as main outcome the presence of voice complaint. The associations between the main outcome and the other variables were performed through the use of chi-square tests and a multiple logistic regression model. Results: The sample consisted mainly of women (87.3%) and the mean age was 24.8 years. The results identified high occurrences of vocal complaints (45.3%) and other health effects related to noise exposure such as stress, communication difficulties, lack of attention and headaches. Conclusion. Environmental and organizational conditions and health effects were not only significantly associated, but also increased the chance of a call center operator reporting voice complaints.